CROWDFUNDING MODELS AND INVESTOR RISKS ASSOCIATED WITH CROWDFUNDING - Kalandarov Aminjon Amondullayevich (Scholar Express Journal, 2022)
Crowdfunding is a way to finance or capitalize a successful business by amassing a large number of little contributions using an online funding platform. It is a modern, cutting-edge adaptation of a long-standing practice. This article discusses the essence of crowdfunding, its pros and cons, the types of crowdfunding models. This article also looks into five different risks or issues associated with crowdfunding for investors.
Keywords: Crowdfunding models; campaign; risks; fraud